HUBUNGAN PEMILIHAN TEMPAT MEMBACA TERHADAP KEBETAHAN MEMBACA DAN KEMAMPUAN BERPIKIR MAHASISWA - Tampubolon, Angela Christysonia; Farasa, Nisa; Kusuma, Hanson E. (Jurnal Koridor, 2017)
The selection of location is fathomed to influence different responses to students when reading. This study chose college students as respondents because reading is a daily learning process related to education or because of individual interests. College students choose a certain locations for reading and the relation between locations and respondents cause the responses to activity. Based on these, this study aimed to find the relation between the chosen reading locations and the students responses when doing reading activity. This study used quantitative research methods and online questionnaire as data collection instruments. To interpret the relations between reading locations and students reading responses, this study used explanatory quantitative research methods. Through open-ended question about the reason for selecting a certain location to read, was found that students reading responses are â€œThinking Abilityâ€ and â€œReading Attachmentâ€. College students choose some certain reading locations, but the majority of students tend to choose rooms and libraries. The results showed three reading clusters. In the first cluster â€œCampus and Public Spacesâ€, was found that the ability to think and students reading attachment tended to be low. In the second cluster â€œEating Areaâ€, was found that students tended to have the attachment of reading but still have difficulty to focus. While in the third cluster, â€œHome Environmentâ€ was found as the ideal reading environment because the ability to think and students reading attachment tended to be high.